Newspaper Management Problems in Nigeria: A Study of Defunct Compass Newspaper (Journal of Management and Social Sciences, 2022)
This paper explored certain problems of newspaper management that confront newspapers in Nigeria and particularly Compass Newspaper. This paper particularly analysed the characteristics of the newspapers as it relates to departmental, structures, and management problems associated with the defunct Compass Newspaper. Different levels of management problems and types based on human or material and also internal and external challenges are identified. The study has a singular objective of unravelling the mystery behind the death of Compass Newspaper as the paper entered the market with lots of promise. In-depth interview was the method used to collect data from the purposely selected management staff, circulation, and account unit staff respectively. The findings showed that the newspaper’s demise was a result of its political partisanship, corruption, and disloyalty among the staff. Therefore, the paper concludes that the type and level of management problems hinder the growth and development of newspapers in the country. The process of founding, managing, and sustaining newspaper from the initial ‘new-to-the-market’ status, to competing with the already known and acceptable ones and other newcomers pose a serious challenge to the industry. The paper concluded that newspaper companies that are building up their first core capabilities still have problems related to a lack of knowledge of management workings. This sets up specific issues for knowledge management in newspaper firms. This research is based on a detailed case study about the major management problems associated with, but not limited to, Nigerian newspapers.Keywords    Newspaper management, survival, challenges, newspaper mortality